Analysis of the Body Shop’s Green Marketing Mix Strategy: A Case Study on the Implementation of Bring Back Our Bottles and Refill Station Programs as a Sustainable Innovation (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In response to the escalating challenge of packaging waste in the beauty industry, The Body Shop Indonesia has implemented a Green Marketing Mix through its Bring Back Our Bottles (BBOB) and Refill Station programs. This study aims to analyze the strategic implementation of this approach, assess consumer perceptions and engagement, and explore the inherent challenges and opportunities for future development. Employing a qualitative case study approach, the research collected data from five respondents who are The Body Shop consumers with prior participation in either the BBOB or Refill Station programs. Data were gathered through semi-structured interviews, observation, and a comprehensive literature review. Thematic analysis was subsequently performed, with findings validated through source and method triangulation. The results indicate that The Body Shop’s Green Marketing Mix has been effectively implemented, particularly in the elements of product (environmentally friendly packaging), promotion (campaigns via digital and print media), and physical evidence (store design that promotes a natural ambiance). Despite positive consumer responses and a strengthened brand image, persistent obstacles were identified, including limited access to program locations and insufficient information dissemination. The programs were found to be effective in enhancing customer loyalty and hold significant potential for expansion, particularly through targeted education and collaborative initiatives with youth communities. This study recommends expanding the programs’ geographical coverage, strengthening digital communication, and establishing strategic community partnerships. The findings are expected to make a meaningful contribution to the development of sustainable green marketing strategies within the beauty industry.